Pediatric Irritable Bowel Syndrome: Perspectives on Pain and Adolescent Social Functioning. Issue 2 (5th April 2018) - Donovan, Elizabeth; Martin, Sarah R; Lung, Kirsten; Evans, Subhadra; Seidman, Laura C; Cousineau, Tara M; Cook, Elizabeth; Zeltzer, Lonnie K
Abstract: Objective: The goal of the study was to describe the experiences of adolescents with irritable bowel syndrome (IBS) from the perspective of adolescents, their parents, and health care providers who treat adolescents who have IBS. Design: The study consisted of semistructured interviews. Setting: Participants were recruited from multidisciplinary pain clinics. Subjects: Thirty-six people participated in the study: 12 adolescents, 12 parents, and 12 health care providers. Results: Two main themes associated with the impact of IBS on adolescents' social functioning emerged from the qualitative interview data: 1) disconnection from peers and 2) strain on family relationships, with subthemes reflecting the perspectives of adolescents, parents, and health care providers. Conclusions: Participants in our study described that adolescents with IBS encounter significant peer- and family-related social stress. Helpful interventions may be those that focus on social support from other adolescents with similar conditions, as well as family-based therapeutic interventions.